Etnopedagogi Kesenian Debus Sebagai Media Pendidikan Karakter Peserta Didik di Sekolah Menengah Kejuruan - Firdaus, Hendi; Hidayar, Sholeh; Leksono, Suroso Mukti; Jamaludin, Ujang (Universitas Mathla'ul Anwar Banten, 2023)
Learning at all levels of education, from elementary school to senior high school, must contain local content. Learning and preserving local wisdom values is the primary concern of education. Debus art contains several values that can shape character and religious values contained in Debus art, namely piety to God Almighty, patience, cooperation, independence, hard work, discipline, and tolerance. The method used in this research is descriptive qualitative. This method starts with collecting, analyzing, and interpreting data. The description method in its implementation was carried out as follows: Interview techniques, case studies (differentiating cases), comparative studies, behavior analysis, and document analysis. This research was carried out on students of SMKN 4 Kota Serang class XI TKRO. Debus is part of the diversity of arts and culture of the people of Banten. Debus's art exemplifies that internal culture in schools will emerge when students apply character education at school. Students are used to living with positive things. Students know their behavior is wrong, but they cannot get used to avoiding it. Debus art forms character in students, such as students having piety to God Almighty, a sense of cooperation, responsibility, discipline, hard work, morality, and ethics by the demands of an independent curriculum, namely developing the potential of students and improving the quality of education.